Structural and morphometric evaluation of the lumbar plexus and its branches: Focus on lumbar nerve roots (Asian Journal of Medical Sciences, 2025)
Background: Variations in Lumbar plexus anatomy can affect surgical and anaesthetic outcomes. Despite the documented general anatomy, detailed morphometric measurements of lumbar nerve roots and branches remain limited, especially in the Indian population. Understanding these morphometric characteristics is crucial for nerve reconstruction, identification of nerve pathologies, and radiological interpretation.Aims and Objectives: This study aims to provide a detailed morphometric analysis of the lumbar plexus and to establish statistical correlations between measurements while examining branching patterns.Materials and Methods: This cadaveric study included 100 specimens used for routine undergraduate dissection in the anatomy department.Results: The ventral rami of L1-L4 spinal nerves were present in all dissected lumbar plexuses. One specimen showed a T12 contribution, and four specimens received L5 contributions. The genital and femoral branches were seen as separate branches piercing the psoas major in 43% of specimens. The accessory obturator nerve (ON) was observed in 16% of specimens. The lateral femoral cutaneous nerve originated from the femoral nerve (FN) in 6% of cases. Statistically, the thickness of L3 and L4 roots was found to be positively correlated, independent of L1. A significant negative correlation was found between the femoral and ONs and the L3 and L4 roots. The ilioinguinal nerve had the longest course, whereas the FN had the shortest. The thickest nerve was the FN, and the thinnest was the ilioinguinal nerve.Conclusion: Morphometric knowledge can be useful during procedures, such as lumbar plexus blocks, estimating nerve root compression risks, selecting donor nerves for grafts, and planning nerve rehabilitation.